(untitled) - Quast, Danny H. (New York, 2004)
Inspired by the author's long-running seminar "Golf Course Maintenance for the Club Manager," this reference offers a wealth of common sense, practical solutions and tips to golf course superintendents and other turf management professionals.
Keywords: Turf management,Golf courses; Maintenance